Implementing a 3d game in unity - Campanella, Francesco (2015)
This project consisted in developing a 3D videogame using a modern 3D game engine. A game engine is a piece of software that provides a wide range of modules and interfaces to develop a videogame. The aim of this project was to verify whether it is possible for an independent developer, with limited resources, to produce a high-quality videogame. Unity 3D was selected as game engine for this project. The graphics and sound content were obtained from the online store on the Unity website and from a company that offers this type of services (Mixamo). The game created is an Adventure Hack and Slash. As such, the game mainly focus on a storyline and on the combat system, allowing the player to improve its combat skills. The main objective in the game is to fight your way out of each level, until the end of the game. The title of the game is Shadow Walker. The tools used allowed to produce a game of reasonably high-quality, considering the limited resource available to the developer. A demonstrational video of the Shadow Walker is available at: https://www.youtube.com/watch?v=3qtm1D3xJc4